2001
DOI: 10.1097/00004770-200105000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Endotoxin by Endodontic Irrigants and Calcium Hydroxide

Abstract: The effects of endodontic irrigants and calcium hydroxide on lipopolysaccharide (LPS; endotoxin) were analyzed using the highly selective technique of mass spectrometry/gas chromatography with selected ion monitoring. An aqueous solution of LPS was mixed with one of a variety of endodontic irrigants for 30 min. Because it is a commonly used interappointment dressing, calcium hydroxide was also applied to LPS for 1, 2, or 5 days. LPS inactivation was measured by quantitation of free fatty acid release. Water, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
15

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 10 publications
2
56
1
15
Order By: Relevance
“…Ethanol showed little breakdown of LPS in a study of detoxification of endotoxin. 18 In our results, LPS was still able to bind to polyethylene particles even in ethanol solutions and simply washing with ethanol did not significantly decrease the amount of LPS on polyethylene particles. Interestingly, Triton X-100 decreased the attachment of LPS to polyethylene particles by 90% in our results.…”
Section: Discussionsupporting
confidence: 39%
“…Ethanol showed little breakdown of LPS in a study of detoxification of endotoxin. 18 In our results, LPS was still able to bind to polyethylene particles even in ethanol solutions and simply washing with ethanol did not significantly decrease the amount of LPS on polyethylene particles. Interestingly, Triton X-100 decreased the attachment of LPS to polyethylene particles by 90% in our results.…”
Section: Discussionsupporting
confidence: 39%
“…Both chlorhexidine and NaOCl have been demonstrated to have no significant effects on bacteria lipopolysaccharide. 60 Chlorhexidine has been shown to be less toxic than NaOCl, 9,61 though a comparative study using fluorescence assay on human periodontal ligament cells showed corresponding cytotoxicity with 0.4% NaOCl and 0.1% chlorhexidine. 62 Chlorhexidine exhibits substantivity to dentin and consequently may present residual antimicrobial effects for days to weeks and help prevent root canal reinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Although CHX does have an antibacterial effect, its tissue dissolution ability is not good. EDTA, NaOCl, CHX, CHX chloride and ethanol have been shown to have little or no detoxifying ability for endotoxin -lipid A (17). On the other hand, calcium hydroxide has been shown to mediate degradation of bacterial lipopolysaccharide (18).…”
Section: Sundqvist Et Al (15) De-mentioning
confidence: 99%